2013
DOI: 10.1371/journal.pone.0065978
|View full text |Cite
|
Sign up to set email alerts
|

Novel 5′ Untranslated Region Directed Blockers of Iron-Regulatory Protein-1 Dependent Amyloid Precursor Protein Translation: Implications for Down Syndrome and Alzheimer's Disease

Abstract: We reported that iron influx drives the translational expression of the neuronal amyloid precursor protein (APP), which has a role in iron efflux. This is via a classic release of repressor interaction of APP mRNA with iron-regulatory protein-1 (IRP1) whereas IRP2 controls the mRNAs encoding the L- and H-subunits of the iron storage protein, ferritin. Here, we identified thirteen potent APP translation blockers that acted selectively towards the uniquely configured iron-responsive element (IRE) RNA stem loop i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 48 publications
(97 reference statements)
1
50
0
Order By: Relevance
“…Briefly, after translation and assembly to the cytoplasm membrane, APP is cleaved by β-secretase originating sAPP and a β-APP C-terminal fragment. The latter is then cleaved by other secretases originating the Aβ peptides [55,56]. Here, we show that APP mRNA expression is decreased in AD patients PBMCs.…”
Section: Discussionmentioning
confidence: 60%
“…Briefly, after translation and assembly to the cytoplasm membrane, APP is cleaved by β-secretase originating sAPP and a β-APP C-terminal fragment. The latter is then cleaved by other secretases originating the Aβ peptides [55,56]. Here, we show that APP mRNA expression is decreased in AD patients PBMCs.…”
Section: Discussionmentioning
confidence: 60%
“…The depletion of NMDAR is subsequently followed by synaptic loss and cell death via the FYN pathway 121 . The misfolding of PrPc into PrP-scrapie in Cruetzfeldt-Jakob disease leads to iron dyshomeostasis and elevated PrP Sc has been found in the AD brain 122,172 .…”
Section: Neuronmentioning
confidence: 99%
“…Kirsch and his collaborators reported decreased levels of copper and increased expression of amyloid β precursor protein (AβPP) in the hippocampus of Irp2 −/− mice suggesting that IRP2 may have a significant role in Alzheimer’s disease (Mueller et al, 2009). Recently, Rogers and his colleagues found that the amyloid precursor protein (APP) also has an IRE-like RNA stem loop in its 5′ untranslated region, and that IRP1 selectively binds to this APP IRE in human neural cells (Bandyopadhyay et al, 2013, 2014; Cho et al, 2010). High expression of Irp1 in the cortex suggests that Irp1 might play an important role in Alzheimer’s disease.…”
Section: Iron Regulatory Proteins and Alzheimer Diseasementioning
confidence: 99%